Tree functional traits, forest biomass, and tree species diversity interact with site properties to drive forest soil carbon - Augusto, Laurent; Boča, Antra (Nature communications, 2022)
Forests constitute important ecosystems in the global carbon cycle. However, how trees and environmental conditions interact to determine the amount of organic carbon stored in forest soils is a hotly debated subject. In particular, how tree species influence soil organic carbon (SOC) remains unclear. Based on a global compilation of data, we show that functional traits of trees and forest standing biomass explain half of the local variability in forest SOC. The effects of functional traits on SOC depended on the climatic and soil conditions with the strongest effect observed under boreal climate and on acidic, poor, coarse-textured soils. Mixing tree species in forests also favours the storage of SOC, provided that a biomass over-yielding occurs in mixed forests. We propose that the forest carbon sink can be optimised by (i) increasing standing biomass, (ii) increasing forest species richness, and (iii) choosing forest composition based on tree functional traits according to the local conditions. Forests constitute important ecosystems in the global carbon cycle. This study investigates how tree species influence soil organic carbon using a global dataset, showing the importance of tree functional traits and forest standing biomass to optimise forest carbon sink.